2000
DOI: 10.1007/s001040050004
|View full text |Cite
|
Sign up to set email alerts
|

Operative Therapie des Echinococcus granulosus (cysticus)

Abstract: Hydatid disease, still frequent in endemic areas, is usually localized in the liver. Despite the benign nature of the disease it is one of the problematic fields of surgery due to the high complication rate and long hospital stay. Based on our experience we recommend evacuation of the cyst and omentoplasty as the surgical method of choice, as it is associated with a relatively low incidence of complications and can be performed easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
12
0
6
Order By: Relevance
“…However, with more conservative procedures, the rate of recurrence reaches 12%. 1,4,8,[10][11][12][13][14][15][16][17] Our results are in line with these reports, since statistical analysis indicated that the most important determinants for recurrence of hydatid cysts were rupture and minute spillage of the hydatid cyst, missing the cysts pre-or intraoperatively and incomplete pericystectomy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, with more conservative procedures, the rate of recurrence reaches 12%. 1,4,8,[10][11][12][13][14][15][16][17] Our results are in line with these reports, since statistical analysis indicated that the most important determinants for recurrence of hydatid cysts were rupture and minute spillage of the hydatid cyst, missing the cysts pre-or intraoperatively and incomplete pericystectomy.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is a trade-off between a low recurrence rate and increased mortality associated with the procedure. 1,8,13,16,17 In our clinic, we do not usually perform radical excisions, which entail increased mortality, for such nonmalignant disease. We usually perform radical excisions in selected patients without any comorbid diseases, especially in patients with solitary cysts located peripherally, with good long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, echinococcal infection of the liver can cause systemic problems like sepsis due to bacterial translocation and/or allergic complications resulting from rupture of the cysts and host sensitization. Local complications include cholestasis, cholangitis and pancreatitis [2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Invasion of the spleen is relatively rare. Splenic hydatidosis is seen in the third place in the order of frequency after hepatic and lung invasion [1, 2, 3]. Primary splenic hydatidosis is quite rare.…”
Section: Introductionmentioning
confidence: 99%